Plant-Made Nervous Necrosis Virus-Like Particles Protect Fish Against Disease - Marsian, Johanna; Hurdiss, Daniel L.; Ranson, Neil A.; Ritala, Anneli; Paley, Richard; Cano, Irene; Lomonossoff, George P. (Frontiers in Plant Science, 2019)
Virus-like particles (VLPs) of the fish virus, Atlantic Cod Nervous necrosis virus (ACNNV), were successfully produced by transient expression of the coat protein in N. benthamiana plants. VLPs could also be produced in transgenic tobacco BY-2 cells. The protein extracted from plants self-assembled into T = 3 particles, that appeared to be morphologically similar to previously analysed NNV VLPs when analysed by high resolution cryo-electron microscopy. Administration of the plant-produced VLPs to sea bass (Dicentrarchus labrax) showed that they could protect the fish against subsequent virus challenge, indicating that plant-produced vaccines may have a substantial future role in aquaculture.